PECULIARITIES OF NUTRITION IN NEWBORNS WITH DIFFERENT DISORDERS TREATED IN NEONATOLOGIС HOSPITALS. EXPERIENCE OF FEEDING WITH ADAPTED MILK MIXTURE - N.V. Degtyareva ("Paediatrician" Publishers LLC, 2010)
The article analyzes an experience of nutrition in children with different disorders (infectious and not infectious diseases) with adopted mixture «Agusha Gold 1». Mixed feeding with dried adopted mixture provides stable increase of child's body mass. This effect is related to optimal composition of mixture and inclusion of probiotic cultures and prebiotic fibers in it.Key words: newborns, mixed feeding, dried adopted mixture, body mass.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):110-112)